Implementation of Management Control Systems in Public Sector Organizations: The Case of Moroccan Universities - ARBAOUI, Saif-Eddine; OUBOUALI, Youssef (Revue du contrôle, de la comptabilité et de l’audit, 2021)
The purpose of this paper is to investigate how management control, as a management tool imported from the private sphere, can be implemented in a Public Sector Organization. The paper employs non-participant observation and semi-structured interviews to explore the determinants of adoption and implementation of management control systems in Moroccan universities. In addition, we have used a documental analysis to explore and diagnose managerial dysfunctions and reform initiatives of Moroccan higher education institutions. We have identified six determining variables in the implementation of management control in the Moroccan university. We have classified these variables into two sets, representing managerial and cultural determinants. Furthermore, we have proposed a conceptual model for the integration of management control in the organizational structure of the Moroccan university. The interest of this research paper stems from the topicality of public management issues in the era of the new Moroccan constitution of 2011 and successive reforms of public finance system. The new managerial philosophy highlights the contribution of management instruments previously reserved for private enterprises in the modernization of Public Sector Organizations. This paper sets out a roadmap for a safe importing of management control to the university, considered as a pilot public organization and a knowledge-creator.